Pengaruh Harga Dan Kualitas Produk Terhadap Kepuasan Pelanggan Tempe - Tri Widyastuti (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2017)
Customer satisfaction is the level of customer ratings of products or services. Manufacturers and traders need to consider the level of customer satisfaction by improving product quality, service quality, price and customer emotional level, as well as production costs. Customer satisfaction measurement provides information for producers, traders and consumers of the products or services produced. This study uses descriptive quantitative method, distributing randomly questionaire to the “Tempe” customers at Pasar Lembang, Kota Tangerang. The evidence from the results obtained from the calculation showed that there is a significant influence partially and simultaneously of price and product quality to customer satisfaction of tempe at Lembang Traditional Market, Kota Tangerang. It can be concluded that the traders and producers should maintain and improve the quality of their products and give the compatible price of the products ‘Tempe” in accordance with their qualities in order to increase the purchasing power and consumer loyalty in consuming the product. Keywords: Pricing, Product Quality, Customer Satisfaction.